Women in medical education: views and experiences from the Kingdom of Saudi Arabia. Issue 8 (August 2016) - Alwazzan, Lulu; Rees, Charlotte E
Abstract : Context: Although research from Western contexts suggests that considerable inequalities for female medical educators exist in the workplace, we do not yet know the views and experiences of women within non‐Western contexts. By examining the influence of context, intersecting identities and language use, this study explores female medical educators' views and experiences of gender, career progression and leadership in academic medicine in the Kingdom of Saudi Arabia (KSA). Methods: We conducted individual interviews employing narrative interviewing techniques with 25 female medical educators from five schools in the KSA (June to December 2014). Data were analysed using framework analysis and drew on intersectionality theory. Results: Participants expressed their views and experiences of career progression, leadership and gendered workplace cultures. Women's experiences of career progression and leadership in the KSA were influenced by their gender and varied according to their career stage, work environment and specialty. Participants discussed the gendered organisational cultures of academic medicine in the KSA in terms of gender inequalities (e.g. females being overlooked for leadership positions), gender stereotypes (e.g. women perceived as more likely to take part in shared leadership) and gendered specialties (e.g. surgery being male dominated). We revealed women's more tacit understandings about gender, career progression and leadership by examining how they talk (e.g. metaphoric, pronominal and emotional talk). Finally, participants constructed multiple intersecting personal (e.g. female, mother and young) and professional identities (e.g. doctor, teacher and leader) for themselves through their narratives. Conclusion: This study provides important new insights into female medical educators' experiences of career progression and leadership in a non‐Western context. Investment in the future of women's careers in the KSA through faculty development initiatives and equality and diversity policies is now essential to help close the gender gap. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.